2018
DOI: 10.1007/s00259-018-3977-4
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of state of the art PET/CT systems performance harmonisation

Abstract: PurposeThe objective of this study was to explore the feasibility of harmonising performance for PET/CT systems equipped with time-of-flight (ToF) and resolution modelling/point spread function (PSF) technologies. A second aim was producing a working prototype of new harmonising criteria with higher contrast recoveries than current EARL standards using various SUV metrics.MethodsFour PET/CT systems with both ToF and PSF capabilities from three major vendors were used to acquire and reconstruct images of the NE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
141
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 124 publications
(152 citation statements)
references
References 48 publications
9
141
0
2
Order By: Relevance
“…Therefore, we expect in the coming years that, besides hardware developments like digital TOF, postprocessing developments like the implementation of BPL algorithms will enhance the performance of PET at a similar pace as we have seen the last decade. Likely, the EANM will have to continue updating the EARL min-max accreditation limits to keep up with these developments, as they did over the last decade [8,9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we expect in the coming years that, besides hardware developments like digital TOF, postprocessing developments like the implementation of BPL algorithms will enhance the performance of PET at a similar pace as we have seen the last decade. Likely, the EANM will have to continue updating the EARL min-max accreditation limits to keep up with these developments, as they did over the last decade [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, initiatives like the European EARL accreditation system help to set up a methodology to compare results of different institutes and PET/CT scanners by narrowing the SUV results and making them reproducible over time [3,8]. New developments in the hardware of PET/CT scanners and reconstruction methods available force these EARL criteria to be updated frequently [9]. Most modern PET/CT scanners have implemented reconstruction algorithms that were developed over the last decades, applying time of flight (TOF) information and point spread function (PSF) modelling [10].…”
Section: Introductionmentioning
confidence: 99%
“…A limitation of both the qPET method and the DS is their sensitivity to differences in scan reconstructions and voxel sizes [5]. Efforts are currently being made to update harmonizing standards that will allow the impact of newer reconstruction methods on image interpretation to be assessed [34,35]. Standardisation of patient preparation, scan acquisition and reconstruction parameters is required but this applies to both visual and quantitative assessment of response [36].…”
Section: Discussionmentioning
confidence: 99%
“…Recent data suggest that advanced image reconstructions (e.g. PSF, qCLEAR) over-estimate maximum SUV values compared to peak and mean SUV values [35]. Hence peak SUV has recently been proposed instead of maximum SUV for assessing tumour activity.…”
Section: Discussionmentioning
confidence: 99%
“…One important topic is to harmonize readouts to establish clinical standards in particular for the quantification of molecular processes, which is one of the advantages of nuclear imaging methods. Kaalep et al [3] (Tallinn, Estonia) presented a collaborative study (several European and one US centre) investigating the feasibility of harmonizing the performance of state-of-the-art PET/CT systems. They performed phantom studies on the newest time of flight (ToF) PET/CT systems available with resolution modelling/point spread function (PSF) technologies, and showed that it is possible to harmonize the systems’ retard, which may provide the basis for a wider study of system harmonization.…”
Section: Physics and Instrumentationmentioning
confidence: 99%